Legal Analysis Of The Legal Nullibility Of Online Loan Agreements Based On Financial Technology (Fintech) - Siti Marisa Juliama; Saut Parulian Panjaitan; M Syaifuddin (JURNAL HUKUM SEHASEN, 2024)
This research aims to determine the legal nullity of fintech-based online loan agreements as well as forms of legal protection for debtors who enter into fintech-based online loan agreements. This research method uses normative legal research. This data is filtered through records in primary and secondary law, meaning studying and investigating several material materials such as journals, literature and statutory regulations. After collecting the material, then analyze the material using qualitative descriptive methods. The results of this research reveal that financial technology (Fintech)-based online agreements are invalidated if the agreement does not adhere to the basis of Article 1320 of the Civil Code and Article 47 paragraph (2) of Government Regulation Number 82 of 2012 concerning the Implementation of Electronic Systems and Transactions (PP PSTE). Then the form of legal protection for creditors who enter into online loan agreements based on financial technology (Fintech) consists of preventive legal protection and repressive law.